Conversion of cassava rhizome using an in-situ catalytic drop tube reactor for fuel gas generation. (July 2015) - Sornkade, Panchaluck; Atong, Duangduen; Sricharoenchaikul, Viboon
Abstract: The air-gasification of cassava rhizome mixed with Ni/α-Al2 O3 catalyst in a drop tube reactor for production of fuel gas was carried out in this work. The conversion was performed at different temperatures from 873 to 1073 K, equivalence ratio (ER) of 0.2–0.6, and semi-continuous feeding of raw material for 30 min. Gas yields, cold gas efficiency (CGE) and lower heating value of fuel gas (LHV) were compared with non-catalytic cases. Generally, higher temperature and ER significantly improved the performance of cassava rhizome gasification. Similar for both of non-catalytic and catalytic cases, at optimum temperature of 1073 K and ER of 0.6, the maximum gas yields were closed to 80% while yields of char and tar were kept minimal at 4% and 11%, respectively. Addition of prepared catalysts resulted in greater CGE and LHV of 92% and 8.6 MJ/N m 3, respectively, comparing to the non-catalytic case of 61% and 6.36 MJ/N m 3, respectively. Moreover, the measured gas distribution data were comparable with the result obtained from thermodynamics conversion model based on minimization of Gibbs free energy of product gases using elemental composition of cassava rhizome (C3.13 H5.2 O3.52 N0.03 S0.04 .) constrained by mass and energy balances for the system. As a result, the gas product distribution and characteristics obtained from this experimental implied its suitability for heat and power applications. Highlights: One of the very first researches on cassava rhizome gasification. Tendency of higher syngas and lower tar bend with increase temperature and catalyst. Catalyst effective for gasification with high gas yield. An equilibrium model based on Gibbs free energy minimization. A capable performance model for reactor at steady state.